The effect of natural and anthropogenic disturbances on the uncertainty of large-area forest growth forecasts. (10th April 2019) - Melo, L C; Schneider, R; Fortin, M
Abstract: This study aimed to estimate the contribution of disturbances to the uncertainty of forest growth forecasts in the Bas-Saint-Laurent region in Quebec, Canada. We focused on two major disturbances affecting that region: spruce budworm (SBW) outbreaks and harvest activities. Growth forecasts were carried out for a period of 100 years (2003–2103) using ARTEMIS-2009, a stochastic individual-based model. Using the Monte Carlo technique, we simulated four scenarios: a baseline; a harvest scenario; a SBW scenario; and a scenario including both harvest and SBW. Uncertainty estimation was performed using a bootstrap variance estimator that applies to the context of hybrid inference. The results revealed that the total variances increased over time. For the scenarios including SBW, the variances were three to six times greater than those in the scenarios without outbreaks. Harvesting did not greatly contribute to the total variance. We conclude that to reduce the uncertainty of large-area growth forecasts in the Bas-Saint-Laurent, considering SBW dynamics is a crucial issue.